[OP.1A.08] COMPARISON BETWEEN OFFICE AND AMBULATORY BLOOD PRESSURE IN ASSESSING THE REDUCTION OF BLOOD PRESSURE: A META-ANALYSIS. (September 2016) - Soranna, D.; Zambon, A.; Corrao, G.; Parati, G.; Zanchetti, A.; Mancia, G.
Abstract : Objective: Office and 24-h ambulatory (A) blood pressure (BP) measurement are the main techniques to quantify the BP effects of treatment in clinical trials and practice. Several clinical trials have made it clear that the BP reduction as evaluated by the two techniques differs. We performed a meta-analysis to quantify the magnitude of this difference in patients given a variety of drug treatments. Moreover, we stratified the analysis for antihypertensive class. Design and method: A MEDLINE research based on the following inclusion criteria was performed: i) randomized clinical trials published from the 1st of January 1960 to the 9th of July 2015; ii) patients treated with any antihypertensive drug either in monotherapy or in combination; iii) treatment-induced office and 24-h mean BP reduction in the same patients; iv) availability of variability measures of BP reduction or sufficient raw data to calculate it. Fixed and random effect models were fitted to estimate the pooled BP reductions for both techniques on condition that the corresponding estimates were reported by at least three studies. Between study heterogeneity was tested using Q statistics and measured with the I2 index. Publication bias was evaluated using funnel plot and Egger's regression asymmetry test. Results: 41 studies satisfying inclusion criteria and including 8, 171 patients were analyzed. The main results are showed in Table 1. Compared to office 24-h mean BP reduction was always less. The ratio between office and 24-h BP reduction was similar for the different treatments (range 1.4–1.9), its value being somewhat lower for patients under combination treatment and markedly higher and more variable for placebo. Figure. No caption available. Conclusions: The effect of antihypertensive treatment is systematically greater for office than for ABP. The difference is marked and visible for all major antihypertensive drugs as well as for combination treatment as compared to monotherapy.